Comprehensive genomic analysis of Xenorhabdus bovienii strain MEL2.2 - Wipanee Meesil; Liam K. R. Sharkey; Sacha J. Pidot; Aunchalee Thanwisai (PLoS ONE, 2025)
The genome sequences of entomopathogenic bacteria and their functional analyses provide valuable insights for genetic engineering to enhance their use as biocontrol agents. In this study, we examine the draft genome of Xenorhabdus bovienii strain MEL2.2, which was isolated from entomopathogenic nematodes in Melbourne, Australia. The genome of Xenorhabdus strain MEL2.2 spans approximately 4.4 million base pairs and has a G + C content of 44.8%, aligning with known characteristics of the genus. Within the genome, 3,823 protein-coding genes were identified. Functional analysis revealed genes associated with nematode symbiosis and insect virulence. Moreover, 15 biosynthetic gene clusters (BGCs) were detected, potentially responsible for synthesizing various secondary metabolites. Comparative genomic analysis indicated a combination of conserved and strain-specific genes when compared to other Xenorhabdus bovienii strains, suggesting genetic traits that may enhance MEL2.2’s adaptability and pathogenicity. Altogether, these findings offer a foundation for exploring the strain’s utility in further applications.